PSYCHOLOGICAL INTERVENTIONS IN NATIONAL DEFENSE - Firda Nur Isnaini; Zhuda Indra Pratama (The Republic of Indonesia Defense University, 2020)
Psychology is a science that continues to evolve, as well as national defense. Both of these are multidimensional sciences, so there needs to be a discussion about the relationship between roles in academia. This study contains a study of psychological science intervention in national defense and discusses psychology in general in the defense aspect. In the national defense system, psychology plays a strong role. Especially, current threats are not only coming from the military aspect but also the non-military aspect. Psychological intervention is needed in order to strengthen the defense system of Indonesia in facing those threats. Psychological interventions can be used in various aspects of defense. This study is written to see the importance of psychological intervention in national defense, as well as discussing psychology in general in the aspect of defense by using literature studies as a research method. The results of this paper suggest the importance of psychology in national defense, so it is necessary to further study this matter in the development of national defense both in terms of its application and science.